Invasive Rhino-Orbital Mucormycosis in a Middle-Aged COVID-19 Patient: A Case Report - Chowdhury, Forhad Uddin Hasan; Kundu, Animesh Kumar; Aman, Sakib; Arafat, Mohammad Shaharior; Bari, Md Shafiqul; Miah, Md Titu (Journal of Bangladesh College of Physicians and Surgeons, 2025)
Background: COVID-19 has been associated with diverse clinical manifestations, among which rhino-orbital-cerebral mucormycosis is increasingly reported. This severe, invasive fungal infection predominantly affects immunocompromised individuals. High-dose corticosteroid use during severe COVID-19, together with diabetes mellitus, increases susceptibility. Case Presentation: We report one of the earliest cases of rhino-orbital-cerebral mucormycosis in Bangladesh occurring after severe COVID-19 pneumonia in a middle-aged diabetic male. The patient developed right-sided headache, facial pain, and acute vision loss while on corticosteroid therapy. Imaging and histopathology confirmed mucormycosis. Surgical debridement, exenteration of the affected eye, and antifungal therapy with amphotericin B followed by oral posaconazole led to clinical improvement. Conclusion: This case underscores the importance of early suspicion of mucormycosis in diabetic COVID-19 patients treated with corticosteroids and demonstrates the critical value of multidisciplinary management in improving outcomes. J Bangladesh Coll Phys Surg 2025; 43: 298-302